Neurodevelopmental Outcomes of Extremely Low Birth Weight Survivors in Johannesburg, South Africa - Ramdin, Tanusha D.; Saggers, Robin T.; Bandini, Rossella M.; Magadla, Yoliswa; Mphaphuli, Aripfani V.; Ballot, Daynia E. (Frontiers in Pediatrics, 2022)
Background: Improved survival in extremely low birth weight infants (ELBWI) in Sub-Saharan Africa has raised the question whether these survivors have an increased chance of adverse neurodevelopmental outcomes. Objectives: To describe neurodevelopmental outcomes of ELBWI in a neonatal unit in South Africa. Methods: This was a prospective follow-up study. All ELBWI who survived to discharge between 1 July 2013 and 31 December 2017 were invited to attend the clinic. Bayley Scales of Infant and Toddler Development (version III) were conducted at 9 to 12 months and 18 to 24 months. Results: There were 723 ELBWI admissions during the study period, 292 (40.4%) survived to hospital discharge and 85/292 (29.1%) attended the neonatal follow up clinic. The mean birth weight was 857.7 g (95% CI: 838.2 – 877.2) and the mean gestational age was 27.5 weeks (95% CI 27.1 – 27.9). None of the infants had any major complication of prematurity. A total of 76/85 (89.4%) of the infants had a Bayley-III assessment at a mean corrected age of 17.21 months (95% CI: 16.2 – 18.3). The mean composite scores for cognition were 98.4 (95% CI 95.1 – 101.7), language 89.9 (95% CI 87.3 – 92.5) and motor 97.6 (95% CI 94.5 – 100.6). All mean scores fell within the normal range., Conclusion Our study demonstrates good neurodevelopmental outcome in a small group of surviving ELBWI, but these results must be interpreted in the context of the high mortality in this group of infants